FIELD EXPERIMENTS IN MARKETING: A PRACTICAL GUIDE FOR ADDRESSING EXTERNAL VALIDITY AND ETHICAL CHALLENGES IN COLLABORATION WITH FIRMS - Yeni Idayusi; Lukmanul Hakim; Dahrul Aman Harahap (RADJA PUBLIKA, 2026)
This study examines the key challenges and emerging best practices in field experiments, with a particular focus on external validity, ethical concerns, and collaboration with firms. The findings reveal that external validity remains a major limitation, as many studies are context-dependent and confined to single firms or markets, reducing generalizability. Ethical issues, including lack of informed consent and heightened privacy risks in digital environments, emerge as the most critical concern, highlighting the need for stronger ethical frameworks and greater transparency. Collaboration with firms offers valuable opportunities but is often constrained by organizational resistance, data access limitations, and misaligned objectives. The analysis also identifies a gap between the severity of these challenges and the current level of best practice adoption. However, emerging approaches such as multi-site experimentation, transparent ethical protocols, and structured collaboration agreements show promise in addressing these issues. In addition, insights from measurement invariance research emphasize the importance of methodological rigor and improved reporting standards. Overall, the study proposes an integrated framework that balances methodological rigor, ethical responsibility, and practical feasibility. These findings provide actionable guidelines for researchers and practitioners to conduct more reliable, ethical, and impactful field experiments in marketing.